Analysis of the influence of the reluctance of iodine double walled carbon nanotube on an axial flux eddy-current ultra-conducting coupling - Patrick Djomo Ombolo; Chaojun Yang; Boris Joel Kenne Telezing (Discover Electronics)
Abstract This study explores the effect of the reluctance concerning a groundbreaking hybrid ultra-conductive axial flux coupling. The coupling includes permanent magnets (PMs) in the driving disk and a partitioned ultra-conductor alongside adjustable reluctance and copper in the subordinate disk. Ultra-conductors represent an emerging category of materials that demonstrate superconductive properties at standard temperatures and above. The torque distribution and magnetic flux characteristics are reviewed and quantified through a magnetic equivalent network. Given that permeability and conductivity change with temperature and the magnetic field around the ultra-conductor, the fluctuations in eddy-current density are graphed. Utilizing curve fitting, we acquired the polynomial equation for resistance, which enabled us to derive the formula for eddy current density. With this information, we deduced the expressions for bulk conductivity, and relative permeability of the ultra-conductor. These expressions helped us understand how the ultra-conductor’s reluctance varies with temperature. Calculations of force and output torque were executed based on Kirchhoff’s law and ampere’s loop law, taking into account the temperature-dependent variation in reluctance. To enhance the coupling’s operating range, performance was analyzed using a high-temperature ultra-conductor (iodine-doped double-walled carbon nanotube) over a temperature spectrum of 20–400 K. The remarkable alignment of torque simulation results with the proposed model’s calculations confirms their correctness.